S-protected thiolated hydroxyethyl cellulose (HEC): Novel mucoadhesive excipient with improved stability. (25th June 2016) - Leonaviciute, Gintare; Bonengel, Sonja; Mahmood, Arshad; Ahmad Idrees, Muneeb; Bernkop-Schnürch, Andreas
Highlights: A thiolated hydroxyethyl cellulose-cysteamine (HEC-cys) conjugate was generated. Thiol groups were successfully protected using 6-mercaptonicotinamide. These modifications led to improved mucoadhesive properties. Thiolation and S-protection affected HEC susceptibility to enzymatic degradation by polysaccharidases. New conjugates were found to be non-toxic. Abstract: The aim of this study was the design of novel S-protected thiolated hydroxyethyl cellulose (HEC) and the assessment of its mucoadhesive properties and biodegradability compared to the corresponding unmodified polymer. Thiolated HEC was S-protected via disulfide bond formation between 6-mercaptonicotinamide (6-MNA) and the thiol substructures of the polymer. In vitro screening of mucoadhesive properties was accomplished using two different methods: rotating cylinder studies and viscosity measurements. Moreover, biodegradability of these polymers by cellulase, xylanase and lysozyme was evaluated. MTT and LDH assays were performed on Caco-2 cells to determine the cytotoxicity of S-protected thiolated HEC. Thiolated HEC displayed 280.09 ± 1.70 μmol of free thiol groups per gram polymer. S-protected thiolated HEC exhibiting 270.8 ± 21.11 μmol immobilized 6-MNA ligands per gram of polymer was shown being 2.4-fold more mucoadhesive compared to thiolated HEC. No mucoadhesion was observed in case of unmodified HEC. Results were in a good agreement with rheological studies. The presence of free thiol moieties likely caused lower degree of hydrolysis by xylanase, whereas the degradation by both enzymes cellulase and xylanase was more hampered when 6-MNA was introduced as ligand for thiol group's protection. Findings in cell viability revealed that all three conjugates were non-toxic. S-protection of thiolated hydroxyethyl cellulose improved mucoadhesive properties and provided pronounced stability towards enzymatic attack, that makes this excipient superior for non-invasive drug administration over thiolated and unmodified forms.